Enigma of pulmonary hypertension; echocardiography in the crossroads - Roychoudhury, Debasish (Respir Med Case Rep, 2020)
Pulmonary hypertension (PH) with its myriad presentations provides a challenge in its diagnosis and management. Recent WHO classification of pulmonary hypertension as defined at the 5th World Symposium held in Nice, France in 2013 tries to highlight different forms of pulmonary hypertension based on different pathophysiology, clinical presentation and therapeutic strategies [1]. These are classified in 5 groups as follows (1): PAH, (2) PH due to left heart disease, (3) PH due to chronic lung disease and/or hypoxia, (4) chronic thromboembolic PH (CTEPH), and (5) PH due to unclear or multifactorial mechanism. In clinical practice we encounter patients with pulmonary hypertension which is often very difficult to diagnose accurately and therefore presents with therapeutic challenge. Echocardiography plays a vital role in diagnosis and management of this enigmatic disease entity. Due to the complex nature of the disease, there can be some overlaps in various groups of pulmonary hypertension. This is particularly true about the two groups according to WHO classification-pulmonary arterial hypertension (WHO group 1) and chronic thromboembolic pulmonary hypertension (WHO group 3). As clinicians we are often faced with the dilemma of making the correct diagnosis and echocardiography plays a pivotal role in this crossroad. We want to present two cases of pulmonary hypertension with different etiologies as stated above and review literature to elucidate the role of echocardiogram in these cases.